2015
DOI: 10.1016/j.jenvp.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Suspicious minds: Can features of the local neighbourhood ease parents' fears about stranger danger?

Abstract: Please cite this article as: Foster, S., Wood, L., Francis, J., Knuiman, M., Villanueva, K., Giles-Corti, B., Suspicious minds: Can features of the local neighbourhood ease parents' fears about stranger danger?, AbstractDeclines in children's independent mobility are frequently attributed to parents' fears about stranger danger, yet there is limited understanding of the factors that might aggravate (or ease) these concerns. We examined the social and built environment correlates of parents': (1) fears about st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 67 publications
2
21
0
1
Order By: Relevance
“…This is unsurprising given higher density housing is frequently located along major arterial roads, which often attract more vehicular traffic and strangers into the local area 70 . Indeed, parent concerns about traffic and strangers are among the highly cited barriers to children's engagement with the outdoors 68,71 .…”
Section: Housing Densitymentioning
confidence: 99%
“…This is unsurprising given higher density housing is frequently located along major arterial roads, which often attract more vehicular traffic and strangers into the local area 70 . Indeed, parent concerns about traffic and strangers are among the highly cited barriers to children's engagement with the outdoors 68,71 .…”
Section: Housing Densitymentioning
confidence: 99%
“…While we do not know whether this assessment differs from how community members would have ordinarily felt about the area, other research has shown that the presence of others in a public place can decrease fear of crime (Jorgensen et al 2012;Maruthaveeran and van den Bosch 2014;Nasar and Jones 1997). Foster et al (2015) note that the benefit of others present in a public space may depend on whether those others are understood as legitimate users of the space. Thus, the dedicated and accessible nature of a PRV may communicate that people are 'supposed to be' where they are and, therefore, bolster perceptions of safety.…”
Section: Discussionmentioning
confidence: 82%
“…The environment where playing takes place (guided and unguided play) is also important. On the one hand, this relates to general urban planning: more walkable pedestrian-friendly neighbourhoods can help diminish parental perceptions of danger (Foster, 2015) and thus support children's free play. On the other hand, it concerns school and community infrastructure, including classrooms and playgrounds.…”
Section: Supporting Children In Their Playmentioning
confidence: 99%